The addition of phosphorus and potassium fertilizer in the generative stage of Job’s tears affects yield components, yield, and yield quality - Wicaksono, Fiky Yulianto; Khairunnisa, Salma; Nurmala, Tati; Irwan, Aep Wawan (Universitas Padjadjaran, 2023)
Job’s tears (Coix lacryma-jobi L.) is an indeterminate food crop that requires more than one-time application of fertilizer. This study aims to determine the effect of additional doses of phosphorus and potassium at the beginning of the generative phase as side dressing fertilization on yield components, yield, and yield quality of the Job’s tears plant. The research was conducted in dry season March - August 2021 at the Experimental Field of the Faculty of Agriculture, Universitas Padjadjaran at Jatinangor, Sumedang Regency around 750 m above sea level. The experimental design used randomized block design (RBD) consisting of nine treatments and three replications, namely P and K fertilizers, respectively at doses of: 0, 20, 30, 40, and 50 kg/ha through one or two frequencies of fertilization. Data analysis used analysis of variance and Scott-Knott test at 5% significance level. The results showed that the application of phosphorus and potassium fertilizers affected the number of panicles, seed weight, and harvest index, but no one effect on other yield components and yield quality. The yield component and the Job’s tears yield were decreased compared to previous studies, which were carried out in sufficient water conditions.Keywords: Job’s tears, Drought, Phosphorus, Potassium